Navigating the intersection of accounting and Artificial Intelligence: Assessing opportunities and risks - Gambhir, Bhumika; Gupta, Neha; Srinivasan, R. (Indonesian Journal of Sustainability Accounting and Management, 2023)
This paper aims to analyse how accounting professionals perceive the deployment of AI in the accounting field. The paper examines the perceptions of opportunities and risks of AI adoption in accounting. This study examined how demographics affect the way accounting professionals perceive the risks and opportunities of AI adoption. A total of 196 responses were collected from accountants working in different industries. The data was analysed using the Independent Samples t-test and One- Way ANOVA. The findings demonstrated that AI confronts accountants with opportunities and risks. Independent t-tests and one-way analysis of variance (ANOVA) results show no significant difference in the perception of risks in the accounting profession due to the adoption of AI based on gender, but there was a significant difference based on age. The results indicate that the perception of opportunities differs significantly by gender and age. The practical implication for organisations is to use the results of the study to prepare their workforce for the digital transformation caused by AI. This is one of the few empirical studies that take a demographics-based look at the perception of risks and opportunities of implementing AI in the accounting profession.